1966
DOI: 10.1243/pime_conf_1966_181_303_02
|View full text |Cite
|
Sign up to set email alerts
|

Paper 10: Metallurgical Aspects of Rolling Contact Fatigue

Abstract: Metallurgical investigations aided by electron microscopy and associated techniques have been carried out on failed test specimens and bearings from service, to obtain information of use in the elucidation of the mechanisms of failure. Investigations have revealed that cracks initiating rolling contact fatigue can start at the surface and spread into the material, or start below the surface and spread outwards, the more dominant mechanism depending upon prevailing circumstances. Metallographic changes in surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 4 publications
2
28
0
Order By: Relevance
“…10). These bands are parallel in the axial section and are inclined $20-30°to the surface in the circumferential section, which agrees with reported results [11][12][13][14][15]. With detailed SEM imaging, these bands are observed to consist of two regions: (i) a thick dented region (marked by dark arrows in Fig.…”
Section: Comparison With Experimental Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…10). These bands are parallel in the axial section and are inclined $20-30°to the surface in the circumferential section, which agrees with reported results [11][12][13][14][15]. With detailed SEM imaging, these bands are observed to consist of two regions: (i) a thick dented region (marked by dark arrows in Fig.…”
Section: Comparison With Experimental Resultssupporting
confidence: 90%
“…Their formation is attributed to tempering in literature [11,12,15,16]. When first observed by Jones, it was suggested to form via temperature increase during bearing operation [11].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[24,119] The transformed band is often referred to as a whiteetching band or a white shear band in steels, and has received much attention, because it is suggested that the phase transformation temperature is reached in the narrow band of material, supporting the thermoplastic instability theory of shear localization. The white-etching bands have been reported mainly in steels (Trent in 1941, [120] Zener and Hollomon, [1] Carrington and Marie in 1948, [121] Andrew et al in 1950, [122] Welsh in 1957, [123] McIntire and Manning in 1958, [124] Rabinowicz in 1965, [125] Scott et al in 1966 and 1967, [126] Nakajima and Mizutani in 1969, [127] Manion and Stock in 1970, [45] Craig and Stock in 1970, [128] Stock et al in 1971, [129] Wingrove in 1971, [130] Glenn and Leslie, [46] Manion and Wingrove in 1972, [49] Thornton and Heiser, [47] Manganello and Abbott in 1972, [131] Eyre and Baxter in 1972, [132] Backman and Finnegan, [110] Wingrove and Wulf in 1973, [133] Woodward and Aghanm, [50] Cho and Duffy, [55] Meyers and Wittman in 1990, [59] and Zurek [115] ), and in titanium and titanium alloys (Me-Bar and Shechtman, [33] Timothy and Hutchings in 1985, [34,134] Grebe et al, [29] Timothy, [24] Winter in 1975, [135] Zhou, Rosakis, and Ravichandran in 1996, [136,137] Liao and Duffy, [56] and Xu and Meyers in 2003 [138] ) and in aluminum ...…”
Section: Deformed and Transformed Bandsmentioning
confidence: 99%
“…Therefore austenite or martensite at the center of the white lines could be expected to be more stable and, consequently, could be the last temper. However, Scott et al [126] pointed out that the white-etching bands could not show the tempering characteristics of conventional martensite, even when heated to temperatures above normal tempering temperatures; heating to above the austenite temperature, however, could cause a disappearance of the white-etching bands and the formation of a structure indistinguishable from the remainder of the specimen. Based on the selected area electron diffraction (SAED) analysis, they suggested that the white band was supersaturated ferrite, with no resemblance to the normal martensite structure.…”
Section: Deformed and Transformed Bandsmentioning
confidence: 99%